Does the Expansion of Public Long‐Term Care Funding Affect Saving Behaviour?1. (September 2017) - Costa‐Font, Joan; Vilaplana‐Prieto, Cristina
Abstract: We study the effect of further public caregiving subsidies (and expansions of insurance to cover long‐term care) on savings and saving behaviour. Specifically, we examine the unique progressive introduction of a universal public long‐term care subsidy ( Sistema para la Autonomía y Atención a la Dependencia, SAAD) in Spain. We draw on a difference‐in‐difference (DID) strategy to show a contraction of savings after the policy intervention, but only among younger elders who receive primarily cash benefits (unconditional caregiving allowance) as opposed to home help (a contraction ranging between 13 per cent and 39 per cent of the subsidy amount). Reductions in savings by individuals in the second and third quintiles of the income distribution, those aged under 75, those without children and those residing in regions that implemented the reform earlier drive the effect.